Frequency and Factors of High-Degree Atrioventricular Block in Patients with Acute Anterior Wall Myocardial Infarction: High-Degree Atrioventricular Block with Acute Anterior Wall Myocardial Infarction - Khan, Khadija; Mahmood, Mazhar; Khan, Jebran; Khan, Muhammad Farooq Azam; Fatima, Mashal; Hussain, Muhammad Waseem (Pakistan Journal of Health Sciences, 2026)
High-degree atrioventricular block (HAVB) is a serious complication of acute anterior wall myocardial infarction (AWMI), contributing significantly to early morbidity and mortality. Early identification of high-risk patients is essential for timely intervention. Objectives: To determine the frequency, clinical predictors, and in-hospital outcomes of HAVB among patients presenting with acute AWMI. Methods: This cross-sectional study included 78 acute AWMI patients presenting at Rahman Medical Institute from June 2024 to July 2025. Demographic data, clinical characteristics, and ECG findings were recorded. Patients were monitored continuously for the development of HAVB. Outcomes included cardiogenic shock, ICU admission, pacing requirements, and in-hospital mortality. Associations were analyzed using chi-square and logistic regression, with p<0.05 considered significant. Results: The mean age of patients was 56.8 ± 8.2 years, predominantly male 51(65.4%). The majority of patients were in the age group 51–60 years, 31 (39.7%). HAVB occurred in 7 (9%) patients. Older age (>60 years) and diabetes mellitus were significantly associated with HAVB (p=0.03) and (p=0.04), respectively. HAVB was strongly associated with cardiogenic shock (p=0.01), ICU admission (p=0.002), and need for temporary pacing (p<0.001). In-hospital mortality was significantly higher in the HAVB group (p=0.04). On multivariate analysis, HAVB independently predicted mortality (aOR 4.9, p=0.03). Conclusions: HAVB is an important predictor of adverse outcomes in AWMI, particularly among older and diabetic patients. Early monitoring and timely pacing interventions are crucial to improving survival.